2006
DOI: 10.1073/pnas.0604613103
|View full text |Cite
|
Sign up to set email alerts
|

Sialidase enhances spinal axon outgrowth in vivo

Abstract: The adult CNS is an inhibitory environment for axon outgrowth, severely limiting recovery from traumatic injury. This limitation is due, in part, to endogenous axon regeneration inhibitors (ARIs) that accumulate at CNS injury sites. ARIs include myelin-associated glycoprotein, Nogo, oligodendrocyte-myelin glycoprotein, and chondroitin sulfate proteoglycans (CSPGs). Some ARIs bind to specific receptors on the axon growth cone to halt outgrowth. Reversing or blocking the actions of ARIs may promote recovery afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 53 publications
1
61
0
Order By: Relevance
“…Supporting this hypothesis are data demonstrating that sialidase reverses the inhibitory effects of MAG on axon outgrowth from some types of neurons in vitro (13,14,17). The increase in serotonergic fibers caudal to the lesion in the current study and our prior observation that sialidase enhanced axon outgrowth from motor neurons into a peripheral nerve graft (19) provide evidence that sialidase treatment enhances axon outgrowth in vivo. However, V. cholerae sialidase has broad specificity for sialic acids in various linkages to lipids and proteins (21).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Supporting this hypothesis are data demonstrating that sialidase reverses the inhibitory effects of MAG on axon outgrowth from some types of neurons in vitro (13,14,17). The increase in serotonergic fibers caudal to the lesion in the current study and our prior observation that sialidase enhanced axon outgrowth from motor neurons into a peripheral nerve graft (19) provide evidence that sialidase treatment enhances axon outgrowth in vivo. However, V. cholerae sialidase has broad specificity for sialic acids in various linkages to lipids and proteins (21).…”
Section: Discussionsupporting
confidence: 74%
“…Some bacterial sialidases are readily overexpressed as recombinant proteins, are highly stable, and efficiently cleave sialic acid residues from MAG-binding sialoglycans on living neurons without cytotoxicity. Previously, we found that infusion of a recombinant sialidase to the site of a peripheral nerve graft enhanced outgrowth of CNS axons into the graft (19). Here, we report that sialidase enhances motor and autonomic functional recovery and stimulates axon outgrowth after spinal cord contusion injury in the rat, an animal model of the most common type of spinal cord injury in humans (20).…”
mentioning
confidence: 84%
“…The enzymes chondroitinase (ChABC) (for review see [148] ) and sialidase [149,150] , or a combination of the two were shown to decrease growth inhibition [151] . Many groups have shown that administration of ChABC is associated with sensory axonal regeneration [152] and functional recovery [148,152,153] when experimentally introduced following SCi.…”
Section: Functionalizing Biomaterials To Tip the Balancementioning
confidence: 99%
“…Many groups have shown that administration of ChABC is associated with sensory axonal regeneration [152] and functional recovery [148,152,153] when experimentally introduced following SCi. When comparing the two, one group found that sialidase increases axonal regeneration and functional recovery [149][150][151] to a greater degree than either ChABC alone or a sialidase/ChABC combination [151] .…”
Section: Functionalizing Biomaterials To Tip the Balancementioning
confidence: 99%
See 1 more Smart Citation